Analysis of Factors Affecting Strand Tension in Cable-Twisting Equipment and Method for Equilibrated Control - Xiaohang Chen; Weiwei Ye (Applied Sciences, 2023)
To address the issue of tension fluctuations and deviations among the strands during cable-twisting production, it is necessary to establish a relationship model between the centrifugal force, frictional force, and tension experienced by each strand in a single span range under the state of traveling and rotating. Considering the differences of strand alignment at the distribution reel, the effects of centrifugal force and friction on strand tension under different twisting-deflection paths and cylinder-traveling paths should be analyzed. In our study, different stress states of each strand were applied to simulate and verify the tension fluctuations and deviations of every strand under various traveling and deflection paths. The experimental results show that the increasing travel path of the strand cylinder will cause an increase in the average strand tension. Different deflection paths in the distribution reel will affect the range of the strand tension fluctuation. A sliding mode controller based on a discrete system was designed in MATLAB to control the tension fluctuation and deviation among the strands. The results indicated that this control method can effectively reduce the tension deviation between strands, and the average tension fluctuation range of each strand was reduced by 79.5%.